TRACKING AND INFORMING ON THE PROGRESS OF FISHERY PRODUCTS - Прилипко, Татьяна; Коваль, Т.В. (Modern engineering and innovative technologies, 2022)
Tracking and informing on the progress of a food product is the basis for ensuring the identification and proper management of all relevant hazards and risks of food production at each link within the food chain. It was found that the content of toxic el